Organizational communication scholars and U.S. higher education leadership: opportunities and challenges when scholars become administrators - Castor, Theresa; Milburn, Trudy; Eisenberg, Eric M.; Shockley-Zalabak, Pam (Management Communication Quarterly, 2025)
Universities and colleges are organizations that significantly impact students, their communities, and society. This forum explores how organizational communication scholars who are university leaders have applied their scholarly backgrounds to inform their roles. The forum participants engage in the work of being reflective practitioners to shed light on how organizational communication theory can help in negotiating the everyday lived experience of academic leadership. Three key issues are explored: (1) in what ways are organizational communication scholars uniquely positioned to assume a university leadership role? (2) how do communication concepts inform the communication practices of administrators? and (3) how do communication practices contribute to universities as multi-faceted institutions? The participants conclude by reflecting on current challenges in higher education and the potential of organizational communication scholars to play a vital role in navigating those challenges.
Keywords: dept.aa; peer-reviewed